Pengawasan dan Pemeriksaan Pajak serta Penerapan Tax Control Framework - Tambun, Sihar; Aryanto, Yuda (Universitas 17 Agustus 1945 Jakarta, 2024)
This research aims to evaluate and study the application of the cooperative compliance paradigm in tax supervision activities, the application of the cooperative compliance paradigm in tax audit activities, the application of the Tax Control Framework by taxpayers as one of the keys to successful cooperative compliance. This research is a descriptive qualitative research that uses the in-depth interview method to obtain information from sources in the tax supervision and audit function at the Directorate General of Taxes, taxpayers, academics and tax consultants as well as literature studies to enable a more comprehensive analysis of the themes in the research. The results of this research conclude that the majority of sources stated that the cooperative compliance paradigm in tax supervision and audit activities has not been fully implemented. In addition, it is known that the majority of taxpayer sources do not yet have an effective TCF.